Alpha1-Adrenergic Receptor Antagonists Use in Treatment and Prevention of Psychiatric Disorders: A Review - Wadhawan, Abhishek; Banga, Alok; Duan, Yinghui; Mennesson, Michel; Helen Wu, Zhao (Current Psychopharmacology, 2014)
Therapeutic benefits of alpha1-adrenergic antagonists (A1As), namely, prazosin, terazosin and doxazosin, have begun to emerge in a broad range of psychiatric disorders in clinical trials. A1As have shown promise in the treatment of several psychiatric disorders such as posttraumatic stress disorder (PTSD), alcohol dependence, cocaine dependence, nicotine cessation and dementia-related agitation in both animal and human studies. These, and other chronic psychiatric conditions, may be mediated or precipitated by stressful conditions. A1As beneficial effects in these psychiatric disorders are hypothesized via their unique effects on regulating norepinephrine (NE) and corticotrophin releasing factor (CRF), which are two key mediators of stress in the central nervous system (CNS). Despite increasing use of A1As in psychiatric disorders, there is a lack of comprehensive review. Animal studies have suggested that by regulating NE in stressful conditions, A1As can increase the pre-frontal cortical functioning and decrease amygdalar activity. Similarly, rat studies have shown a direct decrease in cerebrospinal fluid (CSF) expression of CRF in rats treated with prazosin in stressful conditions. Thus, A1As may have potential benefit in the treatment and secondary prevention of stress-mediated or precipitated psychiatric disorders. In addition, another beneficial effect of A1As is known to be on improvement of metabolic parameters such as lipid profile and insulin sensitivity.
Keywords: stress